C13 COMPARISON OF MINIMALLY INVASIVE VERSUS CONVENTIONAL THORACIC AORTIC OPERATIONS: EARLY AND MID–TERM RESULTS IN A SERIES OF 624 PATIENTS. (18th May 2022) - Berretta, P; Galeazzi, M; Chiuselli, G; Codecasa, R; Alfonsi, J; Braconi, L; Rapisarda, F; Bonacchi, M; Malvindi, P; Stefano, P; Di Eusanio, M
Abstract: Objective: Despite minimally invasive techniques have gained wider clinical application in cardiac surgery, current evidence on mini thoracic aortic surgery is still limited. The aim of this study was to compare early and mid–term outcomes of patients undergoing proximal thoracic aortic interventions through mini–sternotomy (MS) versus full sternotomy (FS). Methods: Data from 624 consecutive patients undergoing proximal aortic operations through MS (n = 214, 34.3%) and FS (n = 410, 65.7%) at 2 aortic centers, were analysed. Patients with prior cardiac operations and active endocarditis, and those who underwent emergency operation and combined procedures were excluded. Treatment selection bias was addressed by the use of propensity score matching (MS vs FS). After matching, 2 well–balanced groups of 202 patients each were created. Surgical procedures involved aortic valve replacement/repair and ascending aorta replacement in 190 patients (47%), aortic root replacement in 110 patients (27.2%) and isolated ascending aorta replacement in 104 patients (25.7%). Results: The median cardiopulmonary bypass and cross clamp times were 88 and 68 minutes, respectively, with no difference between groups. Overall 30–day mortality was 0.7%, being 1% (n = 2) in patients underwent MS and 0.5% (n = 1) in those underwent FS (p = 0.6). No difference was found in the rates of stroke (MS n = 5, 2.5%; FS n = 5, 2.5%), dialysis (MS n = 1, 0.5%; FS n = 4, 2%), bleeding (MS n = 7, 3.5%; FS n = 7, 3.5%), and blood transfusions (MS n = 67, 33.3%; FS n = 57, 28.4%) (Table 1). Patients receiving MS were associated with a lower incidence of respiratory insufficiency compared with those receiving FS (0% vs. 2.5%, p = 0.03). The median intensive care unit length of stay was 24 and 25 hours in MS and FS group, respectively (p = 0.3), and in–hospital stay was 7 days both in MS and FS group (p = 0.9). Three–year survival rate was 96.6% in patients receiving MS and 95.7% in those receiving FS (p = 0.9). Conclusions: Our findings showed that mini proximal aortic operations can be performed successfully without compromising the proven efficacy and safety of conventional access. In selected patients, MS was associated with very low mortality and morbidity rates. Additionally, MS demonstrated superior clinical outcomes as regards respiratory adverse events, when compared with FS.